Improving economic conditions associated with care pattern and cost changes - Wallace, Harper; Fikri, Kenan; Weinstein, James; Weeks, William (Social Determinants of Health, 2021)
Background: Low economic prosperity is associated with worse health and health outcomes. Dramatic increases in prosperity have been associated with reductions in mortality rates. Methods: We conducted a retrospective serial cross-sectional study of Medicare beneficiaries aged 65 and older who were enrolled in Medicare Parts A and B each year, 2003–2015. We examined local economic conditions in 2000 and 2015 at the Dartmouth Atlas-defined Hospital Service Area level. For quintiles of local economic distress in 2000, and for areas that experienced dramatic improvement or deterioration in local economic distress, we calculated per-capita rates of avoidable admissions, receipt of appropriate primary care services, elective surgery utilization, and total Medicare Parts A and B healthcare spending Results: Beneficiaries who lived in the lowest-prosperity areas had higher rates of avoidable admissions, lower rates of appropriate primary care services, higher rates of elective surgeries, and higher overall healthcare spending than those living in the highest-prosperity areas. Dramatic improvement in local economic conditions was associated with adoption of healthcare utilization closely resembling those of the most-prosperous areas and divergent from that of areas that did not see improvement; further, the most-prosperous areas had healthcare consumption patterns that were “immune” to economic decline. Conclusions: Our findings suggest that improving local economic conditions could have healthcare utilization and quality implications. Policymakers should consider improved healthcare quality and reduced avoidable and potentially unnecessary high-cost care as potential returns on investment in improving local economic conditions, while being mindful of potential increases in care costs.